IMPLEMENTATION OF THE MILTON MODEL PATTERN IN ANIES BASWEDAN'S SPEECH AT THE KAMPANYE KUMPUL AKBAR JIS ON YOUTUBE CHANNEL - Hartati, Rita; Njue Steeven Tarigan; Albert Hezekiah Sanolo Zebua (Bajang Institute, 2024)
Neuro-Linguistic Programming (NLP) methods are an interesting topic in the field of communication and public speaking. One model that is often used is the Milton Model which was developed by Milton Erickson with a focus on language patterns to influence and guide a person's thinking (Campbell, 2015). This model helps speakers convey messages effectively, influence audiences, and achieve certain communicative goals. This research aims to analyze the use of the Milton Model in the speech of Anies Baswedan, Candidate for President of Indonesia 2024-2029, looking at the type of Milton Model pattern used and the purpose of its use. The research results show that Anies Baswedan uses the Milton Model to maintain the audience's focus, understand the election situation, and be aware of the actions that need to be taken, by using Presupposition (15%) which influences the audience's thinking so that the message conveyed is conveyed. easy to understand. This research proves that the Milton Model is effectively used in campaign speeches.